Loss of the E6AP Ubiquitin Ligase Induces p53-Dependent Phosphorylation of Human Papillomavirus 18 E6 in Cells Derived from Cervical Cancer - Vats, Arushi; Skrabar, Neva; Del Sal, Giannino; Banks, Lawrence (Journal of virology, 2022)
This study demonstrates that the knockdown of E6AP from cervical cancer-derived cells leads to an increase in phosphorylation of the E6 oncoprotein. We show that this phosphorylation of E6 requires p53 transcriptional activity and the enzyme DNA PK. This study therefore defines a feedback loop whereby activation of p53 can induce phosphorylation of E6 and which in turn can inhibit p53 transcriptional activity independently of E6’s ability to target p53 for degradation. Cancer-causing human papillomavirus (HPV) E6 oncoproteins contain a well-characterized phosphoacceptor site within the PDZ (PSD-95/Dlg/ZO-1) binding motif (PBM) at the C terminus of the protein. Previous studies have shown that the threonine or serine residue in the E6 PBM is subject to phosphorylation by several stress-responsive cellular kinases upon the induction of DNA damage in cervical cancer-derived cells. However, there is little information about the regulation of E6 phosphorylation in the absence of DNA damage and whether there may be other pathways by which E6 is phosphorylated. In this study, we demonstrate that loss of E6AP results in a dramatic increase in the levels of phosphorylated E6 (pE6) despite the expected overall reduction in total E6 protein levels. Furthermore, phosphorylation of E6 requires transcriptionally active p53 and occurs in a manner that is dependent upon DNA-dependent protein kinase (DNA PK). These results identify a novel feedback loop, where loss of E6AP results in upregulation of p53, leading to increased levels of E6 phosphorylation, which in turn correlates with increased association with 14-3-3 and inhibition of p53 transcriptional activity. IMPORTANCE This study demonstrates that the knockdown of E6AP from cervical cancer-derived cells leads to an increase in phosphorylation of the E6 oncoprotein. We show that this phosphorylation of E6 requires p53 transcriptional activity and the enzyme DNA PK. This study therefore defines a feedback loop whereby activation of p53 can induce phosphorylation of E6 and which in turn can inhibit p53 transcriptional activity independently of E6’s ability to target p53 for degradation.